Interval Waktu Penambahan Ampas Mengkudu (Morinda citrifolia L.) dalam Ransum terhadap Performans Ayam Broiler - Yuni Primandini; Luthfi Djauhari Mahfudz; Bambang Sukamto (Agricultural Faculty, 2012)
Time interval of supplementation of Morinda citrifolia L. by product on the performance broiler chickenABSTRACT. The research using Completely Randomized Design with 3x2 factorial arrangement and 4 replicated. Dose of Morinda citrifolia by product (T) that is 0 g/kg ( T0); 0.50 g/kg ( T1); 0.75 g/kg ( T2) and 1.00 g/kg (T3) as first factor and time interval that is continue (A1) and 1 week interval (A2) as second factor. The performance parameters observed were : feed intake, body weight and small intestine measure. The result showed that no significant effect of time interval and interaction between time interval with Morinda citrifolia by product dose (p0.05) on feed intake and small intestine measure. The addition dose of Morinda citrifolia by product increased (p0.05) body weight, there was interaction (p0.05) between time interval and Morinda citrifolia by product dose on body weight.